Electromagnetic wave absorber and composite for shielding electromagnetic waves

By using fibrous carbon in the electromagnetic wave absorber, adjusting the complex capacity and dispersion state, and designing a resonant electromagnetic wave absorber, the problem of insufficient absorption capacity of high-frequency electromagnetic waves in the existing technology is solved, and the lightweight and efficient electromagnetic wave absorption effect is achieved .

CN119138116APending Publication Date: 2024-12-13TEIKOKU PISTON RING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202280095186.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-05-23
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing electromagnetic wave absorbers lack the electromagnetic wave absorption capacity in high-frequency bands (especially above 18GHz), and the use of soft magnetic metal materials leads to increased weight and poor forming processability.

Method used

Using an electromagnetic wave absorber containing fibrous carbon, a resonant electromagnetic wave absorber on the surface of the metal layer is designed by adjusting the real and imaginary parts of the complex capacity and the dispersion state of fibrous carbon. The network structure of fibrous carbon is used. Improve electromagnetic wave absorption characteristics.

Benefits of technology

The high electromagnetic wave absorption characteristics in the high frequency band exceeding 18GHz are achieved, which reduces the problems of weight increase and poor forming processability, and provides a lightweight and efficient electromagnetic wave absorption effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119138116A_ABST
    Figure CN119138116A_ABST
Patent Text Reader

Abstract

Provided are: an electromagnetic wave absorber; and a composite for shielding electromagnetic waves, which comprises the electromagnetic wave absorber and an electromagnetic wave reflecting layer provided on one surface side of the electromagnetic wave absorber. The electromagnetic wave absorber contains fibrous carbon, the real part of the complex permittivity of the electromagnetic wave absorber at a frequency of 24 GHz is 6-30, the imaginary part of the complex permittivity of the electromagnetic wave absorber is 1-25, and when the electromagnetic wave absorber is cut, the number of fiber bundles of the fibrous carbon and the number of fiber bundles having a maximum diameter of 100 nm or more observed in a cut surface of the electromagnetic wave absorber are less than or equal to 1, and the number of fiber bundles having a maximum diameter of 100 nm or more observed in the cut surface of the electromagnetic wave absorber is less than or equal to 1. And the number of the particles is 10 or less per 10 [mu] m * 10 [mu] m.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an electromagnetic wave absorber containing fibrous carbon and an electromagnetic wave shielding composite using the electromagnetic wave absorber. Background Art

[0002] In recent years, the frequency band of electromagnetic waves used in communication equipment, radar, etc. has been accelerating. In such an electromagnetic environment, electromagnetic wave absorbers are used to suppress malfunctions caused by electromagnetic wave interference between devices or between circuits within devices.

[0003] In recent years, expectations for the fifth generation mobile communication system (5G) have been growing in order to achieve greater capacity and high-speed communications from the previous fourth generation mobile communication system (4G). In 5G, frequency bands above 18 GHz are mostly used. Therefore, in order to prevent malfunctions in high frequency bands, there is an increasing demand for electromagnetic wave absorbers for the purpose of maintaining the electromagnetic wave environment.

[0004] In the prior art, soft magnetic metal materials are used in electromagnetic wave absorbers. However, it is known that in electromagnetic wave absorbers using soft magnetic metal materials, according to the Snoke limit law, the relative magnetic permeability decreases sharply in the GHz band, and the electromagnetic wave absorption capacity also decreases accordingly. In addition, since soft magnetic metal materials are raw materials with high specific gravity, the weight of electromagnetic wave absorbers using soft magnetic metal materials increases, which becomes the main reason that hinders the lightweighting of electromagnetic wave absorbers. In addition, when using soft magnetic metal materials to manufacture electromagnetic wave absorbers on the high-frequency band side, due to the low absorbency, a large amount of absorbing material needs to be mixed, which leads to an increase in weight and poor forming processability.

[0005] In addition, the use of carbon materials as the raw material of the electromagnetic wave absorber has also been studied (see Patent Document 1).

[0006] [Prior art literature]

[0007] [Patent Literature]

[0008] Patent Document 1: International Publication No. 2021 / 230140 Summary of the invention

[0009] (Problems to be solved by the invention)

[0010] Carbon materials have also been studied as materials for electromagnetic wave absorbers, but sufficient absorption characteristics for electromagnetic waves in a high-frequency band exceeding 18 GHz have not been obtained.

[0011] Therefore, an object of the present invention is to provide an electromagnetic wave absorber and an electromagnetic wave shielding composite having high electromagnetic wave absorption characteristics in a high frequency band exceeding 18 GHz by being arranged on the surface of an electromagnetic wave reflecting layer such as a metal layer.

[0012] (Solutions to solve problems)

[0013] The present invention provides the following technical solutions.

[0014] <1> An electromagnetic wave absorber containing fibrous carbon, wherein the real part of the complex permittivity of the electromagnetic wave absorber at a frequency of 24 GHz is 6 to 30, and the imaginary part is 1 to 25; when the electromagnetic wave absorber is cut, the number of fiber bundles of the fibrous carbon observed in the cut surface of the electromagnetic wave absorber and the fiber bundles with a maximum diameter of more than 100 nm is less than 10 per 10 μm×10 μm.

[0015] <2> according to <1> The electromagnetic wave absorber, wherein, when the electromagnetic wave absorber is cut, the ratio of the number of the fiber bundles with a maximum diameter of 5 nm or more and less than 100 nm observed in each 10 μm×10 μm of the cut surface of the electromagnetic wave absorber to the total number of the fiber bundles with a maximum diameter of 5 nm or more and less than 100 nm and the number of the fiber bundles with a maximum diameter of 100 nm or more is 80% or more.

[0016] <3> according to <1> or <2> The electromagnetic wave absorber, wherein the content of the fibrous carbon in the electromagnetic wave absorber is 0.2 to 1.5 Mass %.

[0017] <4> according to <1> to <3> The electromagnetic wave absorber described in any one of the above aspects includes the fibrous carbon and a substrate, wherein the substrate includes at least one selected from the group consisting of a resin, an elastic material, and a rubber.

[0018] <5> according to <4> In the electromagnetic wave absorber, the substrate contains at least one selected from silicone resin, silicone elastic material and silicone rubber.

[0019] <6> according to <1> ~ <5> The electromagnetic wave absorber described in any one of the preceding claims, wherein the fibrous carbon is a carbon nanotube.

[0020] <7> according to <1> or <2> The electromagnetic wave absorber, wherein the electromagnetic wave absorber contains the fibrous carbon and a substrate, the fibrous carbon is carbon nanotubes, the substrate contains at least one selected from silicone resin, silicone elastic material and silicone rubber, and the content of the fibrous carbon in the electromagnetic wave absorber is 0.2 to 1.5 Mass%.

[0021] <8> according to <1> ~ <7> The electromagnetic wave absorber according to any one of the preceding claims, wherein the elongation at break of the electromagnetic wave absorber measured in accordance with JIS K 6251:2017 is 150% or more.

[0022] <9> according to <1> ~ <8> The electromagnetic wave absorber according to any one of the preceding claims, wherein the thickness of the electromagnetic wave absorber is 0.2 to 2.0 mm.

[0023] <10> according to <1> to <9> The electromagnetic wave absorber according to any one of claims 1 to 5, wherein the specific gravity of the electromagnetic wave absorber is 2.5 or less.

[0024] <11> according to <1> to <10> The electromagnetic wave absorber according to any one of the preceding claims, wherein the total light transmittance of the electromagnetic wave absorber measured in accordance with ISO13468 is 20% or less.

[0025] <12> A composite body for electromagnetic wave shielding, comprising <1> ~ <11> The electromagnetic wave absorber described in any one of the above, and an electromagnetic wave reflecting layer provided on one surface side of the electromagnetic wave absorber.

[0026] (Effects of the Invention)

[0027] According to the present invention, an electromagnetic wave absorber and an electromagnetic wave shielding composite having high electromagnetic wave absorption characteristics in a high frequency band exceeding 18 GHz can be provided by being arranged on the surface of an electromagnetic wave reflecting layer such as a metal layer and used.

[0028] The present invention contributes to Goal 3 "Good health and well-being for all" and Goal 12 "Responsible consumption and production" among the 17 goals of SDGs (United Nations Sustainable Development Goals). BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a diagram showing the relationship between the real part and the imaginary part of the complex permittivity satisfying the no-reflection condition.

[0030] Figure 2 This is a graph showing the reflection attenuation amounts of the electromagnetic wave absorbers of Examples 1, 2, and 4.

[0031] Figure 3 This is a graph showing the reflection attenuation amount of the electromagnetic wave absorber of Examples 3 and 5. DETAILED DESCRIPTION

[0032] In the present specification, a numerical range expressed using the symbol “to” means a range including the numerical values ​​described before and after “to” as the lower limit and the upper limit, respectively.

[0033] <Electromagnetic wave absorber>

[0034] The electromagnetic wave absorber of the present invention is an electromagnetic wave absorber containing fibrous carbon, and the electromagnetic wave absorber is characterized in that:

[0035] The real part of the complex permittivity of the electromagnetic wave absorber at a frequency of 24 GHz is 6 to 30, and the imaginary part is 1 to 25; when the electromagnetic wave absorber is cut, the number of fiber bundles of the fibrous carbon and the maximum diameter of which is observed in the cut surface of the electromagnetic wave absorber and is greater than 100 nm is less than 10 per 10 μm×10 μm.

[0036] The electromagnetic wave absorber of the present invention is used by being arranged on the surface of an electromagnetic wave reflecting material such as a metal, and can control the amplitude and phase of the reflected wave from the metal surface and the reflected wave from the front of the electromagnetic wave absorber (the surface opposite to the side on which the metal is arranged) to reduce the reflected wave. Therefore, by using the electromagnetic wave absorber of the present invention on the surface of an electromagnetic wave reflecting material such as a metal, it is possible to effectively absorb electromagnetic waves. An electromagnetic wave absorber that reduces electromagnetic waves based on this mechanism is also called a resonant electromagnetic wave absorber. In a resonant electromagnetic wave absorber, when the following formula called the non-reflection condition is satisfied, there is theoretically no reflected electromagnetic wave.

[0037] [Formula 1]

[0038]

[0039] In formula (1), "tanh" is an operator having a hyperbolic tangent function, "ε" is a complex permittivity, "j" is an imaginary unit, "d" is the thickness of the electromagnetic wave absorber (dielectric layer), and "λ" is the wavelength of the electromagnetic wave.

[0040] Figure 1 , a graph is shown in which the x-axis represents the real part of the complex permittivity of formula (1) and the y-axis represents the imaginary part of the complex permittivity of formula (1). In the case of electromagnetic wave attenuation, the imaginary part is generally large.

[0041] According to the research of the inventors of the present application, after designing the real part and imaginary part of the complex permittivity in a manner close to the above-mentioned non-reflection condition while controlling the properties, state, and dispersion state of the fibrous carbon in the electromagnetic wave absorber, it was found that when a smaller amount of fibrous carbon is added than before, the real part and imaginary part of the complex permittivity can be plotted. Figure 1 The vicinity of the non-reflection curve shown can have high electromagnetic wave absorption characteristics.

[0042] That is, in the electromagnetic wave absorber of the present invention, the real part of the complex permittivity is adjusted to 6 to 30, and the imaginary part is adjusted to 1 to 25. Furthermore, the dispersion state of the fibrous carbon in the electromagnetic wave absorber is adjusted so that the number of fiber bundles (fibrous carbon fiber bundles) with a maximum diameter of 100 nm or more observed in the cross-section of the electromagnetic wave absorber is 10 or less per 10 μm×10 μm. Thus, the complex permittivity of the electromagnetic wave absorber can be plotted at 6 to 30 with a smaller amount of fibrous carbon added than before. Figure 1 The vicinity of the non-reflection curve shown can have high electromagnetic wave absorption characteristics.

[0043] exist Figure 1 In the graph, when the value of d / λ is small, that is, the thickness of the electromagnetic wave absorber becomes smaller relative to the wavelength, the real part and imaginary part of the complex permittivity are located in the small direction on the graph, and when the value of d / λ is large, that is, the thickness of the electromagnetic wave absorber becomes larger relative to the wavelength, the real part and imaginary part of the complex permittivity are located in the large direction. Fibrous carbon forms a network by dispersing in the electromagnetic wave absorber, and is depicted as an equivalent circuit consisting of reactance and capacitance. Therefore, the higher the high frequency band, the greater the loss of electromagnetic waves, and the higher the dispersion, the more fine capacitors exist, so the loss of electromagnetic waves becomes greater. That is, in Figure 1 In the case where the real part of the complex permittivity is the same, if the dispersion of the fibrous carbon is high, the imaginary part of the complex permittivity tends to increase. When the concentration of the fibrous carbon in the electromagnetic wave absorber increases, the complex permittivity of the electromagnetic wave absorber increases, but when the dispersion of the fibrous carbon is high, even if the concentration is increased from a very small amount, there is a concentration that intersects the no-reflection curve, and high electromagnetic wave absorption characteristics can be exhibited.

[0044] That is, in the electromagnetic wave absorber of the present invention, by adjusting the dispersion state of the fibrous carbon in the electromagnetic wave absorber, the number of fiber bundles with a maximum diameter of 100 nm or more observed in the cross-section of the electromagnetic wave absorber is made to be less than 10 per 10 μm×10 μm. Thus, even if the content of the fibrous carbon in the electromagnetic wave absorber is as small as 0.2 to 1.5 Mass%, high electromagnetic wave absorption characteristics can be exhibited.

[0045] The real part of the complex permittivity of the electromagnetic wave absorber of the present invention at a frequency of 24 GHz is 6 to 30, preferably 6 to 25, and more preferably 7 to 20. When the real part of the complex permittivity is within the above range, higher electromagnetic wave absorption characteristics can be obtained in a high frequency band exceeding 5 GHz (particularly preferably a high frequency band exceeding 18 GHz).

[0046] The imaginary part of the complex permittivity of the electromagnetic wave absorber of the present invention at a frequency of 24 GHz is 1 to 25, preferably 1.5 to 20, and more preferably 2 to 15. When the imaginary part of the complex permittivity is within the above range, higher electromagnetic wave absorption characteristics can be obtained in a high frequency band exceeding 5 GHz (especially preferably a high frequency band exceeding 18 GHz).

[0047] As a method for adjusting the real part and imaginary part of the complex permittivity of the electromagnetic wave absorber at a frequency of 24 GHz to the above range, there can be cited methods such as adjusting the content or type of fibrous carbon, dispersibility, etc. In order to improve the dispersibility of fibrous carbon in the electromagnetic wave absorber, there can be cited methods such as: dispersing fibrous carbon in a liquid phase, and then mixing with a substance obtained by dispersing a substrate such as a resin, rubber, or an elastomer in a liquid phase, and then drying and compounding; using a mixer, a roller, etc., to mix and disperse the fibrous carbon in a substrate using a strong shear force. By using fibrous carbon with a long fiber length and a thin fiber bundle, it is easier to adjust the real part and imaginary part of the complex permittivity to the above range even if the fibrous carbon is a small amount. By using such fibrous carbon, the network effect generated by the fibrous carbon is improved, and electromagnetic waves can be absorbed efficiently. In addition, by lengthening the fiber length of the fibrous carbon, the conductivity of the electromagnetic wave absorber is improved, so the loss caused by the fiber resistance can also be improved.

[0048] More specifically, for example, when carbon nanotubes are used as fibrous carbon, by increasing the average length of the carbon nanotubes, the conductivity of the electromagnetic wave absorber can be improved, and the total loss of electromagnetic waves caused by the fiber network can be increased. In addition, by reducing the average diameter of the carbon nanotubes, the imaginary part of the complex permittivity can be increased. According to the above tendency, by increasing the aspect ratio of the carbon nanotubes, that is, increasing the fiber length of the carbon nanotubes and reducing the average diameter, the real part and the imaginary part of the complex permittivity of the electromagnetic wave absorber can be increased. Therefore, even if the mixing amount of the carbon nanotubes is small, the values ​​of the real part and the imaginary part of the complex permittivity of the electromagnetic wave absorber can be made close to Figure 1 The non-reflective curve.

[0049] In the electromagnetic wave absorber of the present invention, the number of fiber bundles with a maximum diameter of 100 nm or more observed in the cross section of the electromagnetic wave absorber is 10 or less, preferably 9 or less, more preferably 8 or less, and further preferably 6 or less per 10 μm×10 μm. When the number of fiber bundles with a maximum diameter of 100 nm or more is 10 or less, the dispersion of the fibrous carbon in the electromagnetic wave absorber is good, and the electromagnetic wave can be effectively absorbed by the conductive loss caused by the increased probability of collision between the electromagnetic wave incident in the electromagnetic wave absorber and the fibrous carbon and the dielectric loss caused by the capacitance between the fibrous carbons, thereby obtaining higher electromagnetic wave absorption characteristics.

[0050] As methods for making the number of fiber bundles with a maximum diameter of 100 nm or more observed in the cut surface less than 10 per 10 μm×10 μm, there can be cited: a method of adjusting the type or content of fibrous carbon; a method of using fibrous carbon in the form of a master batch supported (held) on a carrier polymer material to produce an electromagnetic wave absorber; a method of dispersing by strong shear force using a device such as a kneader or a twin-axis extruder.

[0051] In the electromagnetic wave absorber of the present invention, when the electromagnetic wave absorber is cut, the ratio of the number of fiber bundles with a maximum diameter of 5 nm or more and less than 100 nm observed in each 10 μm×10 μm of the cut surface of the electromagnetic wave absorber to the total number of fiber bundles with a maximum diameter of 5 nm or more and less than 100 nm and the number of fiber bundles with a maximum diameter of 100 nm or more is preferably 50% or more, more preferably 80% or more, and further preferably 90% or more. According to this form, the dispersion of fibrous carbon in the electromagnetic wave absorber is good, and a dense three-dimensional network composed of fibrous carbon is formed in the electromagnetic wave absorber, and the electromagnetic wave can be effectively absorbed by the conductive loss caused by the increased probability of collision between the electromagnetic wave incident in the electromagnetic wave absorber and the fibrous carbon and the dielectric loss caused by the capacitance between the fibrous carbons, thereby obtaining higher electromagnetic wave absorption characteristics.

[0052] It should be noted that in this specification, the fiber bundle observed in the cut surface of the electromagnetic wave absorber means that the fibrous carbon is partially or completely bundled on the cut surface of the electromagnetic wave absorber. On the cut surface of the electromagnetic wave absorber, sometimes a plurality of fiber bundles overlap each other, but when each fiber bundle is an independent fiber bundle, the independent fiber bundles are calculated as one fiber bundle. That is, on the cut surface of the electromagnetic wave absorber, when two fiber bundles with a maximum diameter of 100 nm or more are observed to overlap, the number of fiber bundles with a maximum diameter of 100 nm or more is two.

[0053] The total light transmittance of the electromagnetic wave absorber of the present invention measured according to ISO 13468 is preferably 20% or less, more preferably 15% or less, and further preferably 10% or less. According to this form, the fibrous carbon has good dispersibility in the electromagnetic wave absorber and can effectively absorb electromagnetic waves, thereby obtaining higher electromagnetic wave absorption characteristics.

[0054] The specific gravity of the electromagnetic wave absorber of the present invention is preferably 2.5 or less, more preferably 2.2 or less, and further preferably 2 or less.

[0055] The electromagnetic wave absorber of the present invention preferably has an elongation at break measured according to JIS K 6251: 2017 of 150% or more, more preferably 200% or more, and further preferably 250% or more. In this form, it has flexibility and can be applied to components of various shapes.

[0056] The electromagnetic wave absorption capacity of the electromagnetic wave absorber of the present invention at a frequency of 18 GHz to 110 GHz is measured by measuring the attenuation of the electromagnetic wave incident in a state of being attached to a reflective layer such as aluminum. The minimum peak value of the reflection attenuation of the electromagnetic wave absorber measured in this way is preferably below -15 dB, more preferably below -20 dB.

[0057] The shape of the electromagnetic wave absorber of the present invention is not particularly limited and can be appropriately selected according to the purpose or application. For example, a sheet shape, a plate shape, a rod shape, etc. can be mentioned.

[0058] The thickness of the electromagnetic wave absorber of the present invention is preferably 0.1 to 2.0 mm. The upper limit is preferably 1.8 mm or less, more preferably 1.5 mm or less, and the lower limit is preferably 0.15 mm or more, more preferably 0.2 mm or more.

[0059] (Fibrous Carbon)

[0060] The electromagnetic wave absorber of the present invention contains fibrous carbon. The content of fibrous carbon in the electromagnetic wave absorber is preferably 0.2 to 1.5 Mass%. The upper limit is preferably 1.4 Mass% or less, and more preferably 1.2 Mass% or less. If the content of fibrous carbon is too much, the electromagnetic waves incident on the electromagnetic wave absorber are easily reflected near the surface of the electromagnetic wave absorber, and there is a tendency that it is not easy for the electromagnetic waves to enter the electromagnetic wave absorber. When the content of fibrous carbon is within the above range, a three-dimensional network structure composed of fibrous carbon is easily formed in the electromagnetic wave absorber. Since such a three-dimensional network structure is formed in the electromagnetic wave absorber, it is possible to effectively absorb electromagnetic waves through the conductive loss caused by the increased probability of collision between the electromagnetic wave incident on the electromagnetic wave absorber and the fibrous carbon and the dielectric loss caused by the capacitance between the fibrous carbons, thereby being able to form an electromagnetic wave absorber having excellent electromagnetic wave absorption characteristics in the high-frequency band.

[0061] Examples of the fibrous carbon include carbon nanotubes, carbon nanofibers, carbon nanohorns, and carbon fibers. Among them, carbon nanotubes are preferred.

[0062] A carbon nanotube is a material in which a graphene sheet is formed into a single-layer or multi-layer tube shape. The carbon nanotube in this specification also includes a conical material called a carbon nanohorn.

[0063] The carbon nanotubes may be single-layer carbon nanotubes or multi-layer carbon nanotubes. From the perspective of various properties such as mechanical properties, electrical conductivity, thermal conductivity, etc., or material cost, the carbon nanotubes are preferably single-layer to 20-layer carbon nanotubes, more preferably single-layer to 15-layer carbon nanotubes, and further preferably single-layer to 10-layer carbon nanotubes. Both ends of the carbon nanotubes may be open, or either or both may be closed.

[0064] The average diameter of the carbon nanotubes is preferably 0.03 to 200 nm. The lower limit of the average diameter is preferably 1 nm or more, more preferably 3 nm or more, and further preferably 5 nm or more. The upper limit of the average diameter is preferably 150 nm or less, more preferably 100 nm or less, and further preferably 50 nm or less.

[0065] The average length of the carbon nanotubes is preferably 0.0005 to 3 mm. The lower limit of the average length is preferably 0.0006 mm or more, more preferably 0.0008 mm or more, and further preferably 0.001 mm or more. The upper limit is preferably 3 mm or less, more preferably 2.5 mm or less, and further preferably 2 mm or less.

[0066] The average aspect ratio of the carbon nanotubes is preferably 50 to 500,000. When the average aspect ratio of the carbon nanotubes is within the above range, even a small amount of mixing can obtain higher electromagnetic wave absorption characteristics in the high-frequency band exceeding 5 GHz (especially preferably the high-frequency band exceeding 18 GHz). The lower limit of the average aspect ratio of the carbon nanotubes is preferably 100 or more, more preferably 150 or more, further preferably 200 or more, further preferably 1,000 or more, and particularly preferably 10,000 or more. The upper limit of the average aspect ratio of the carbon nanotubes is preferably 450,000 or less, more preferably 400,000 or less, and further preferably 300,000 or less. It should be noted that in this specification, the average aspect ratio of the carbon nanotubes refers to: the ratio of the average length to the average diameter of the carbon nanotubes (average length / average diameter).

[0067] In this specification, the average diameter of carbon nanotubes is a value calculated by measuring the diameters (outer diameters) of 30 randomly selected carbon nanotubes using a scanning electron microscope or a transmission electron microscope and finding the average value thereof. In addition, the average length of carbon nanotubes is a value calculated by measuring the lengths of 30 randomly selected carbon nanotubes using a scanning electron microscope or a transmission electron microscope and finding the average value thereof.

[0068] The specific surface area of ​​the carbon nanotubes is preferably 100 to 800 m 2 / g. The lower limit of the specific surface area is preferably 150m 2 / g or more, more preferably 200m 2 The upper limit of the specific surface area is preferably 550 m 2 / g or less, more preferably 500m 2 In this specification, the specific surface area of ​​carbon nanotubes is a value of a BET specific surface area measured by a gas adsorption method (multipoint method) in accordance with JIS Z8830 (ISO9277).

[0069] Carbon nanotubes can be produced by known methods such as arc method, laser ablation method, chemical vapor deposition method (CVD method), etc. Alternatively, they can be produced by the method described in paragraphs 0029 to 0038 of Japanese Patent Application Laid-Open No. 2020-180251.

[0070] In carbon nanotubes, acidic groups or basic groups can be introduced on the surface by oxidation treatment or modification with a high molecular weight polymer. Examples of the acidic group include carboxyl groups, and examples of the basic group include amine groups.

[0071] In the electromagnetic wave absorber of the present invention, it is preferred that carbon nanotubes are contained in the form of a masterbatch supported on a carrier polymer material. Carbon nanotubes are bulky and easily condensed raw materials. By using carbon nanotubes in the form of a masterbatch supported on a carrier polymer material, the condensation of carbon nanotubes during the manufacture of the electromagnetic wave absorber can be suppressed, thereby forming an electromagnetic wave absorber with excellent dispersibility of carbon nanotubes. In addition, when manufacturing the electromagnetic wave absorber, even if excessive dispersion treatment is not performed, an electromagnetic wave absorber with excellent dispersibility of carbon nanotubes can be obtained, so that the breakage of carbon nanotubes caused by mechanical shearing can be suppressed, and the high aspect ratio of carbon nanotubes can be maintained. In addition, since the dispersibility of carbon nanotubes in the electromagnetic wave absorber can be improved, the dielectric loss in the high frequency band becomes larger, and the electromagnetic wave absorption characteristics in the high frequency band can be further improved.

[0072] As the carrier polymer material of the carbon nanotube, there is no particular limitation, and resin, elastic material and rubber etc. can be cited. The resin can be a thermoplastic resin or a thermosetting resin. As the resin, known materials can be cited, for example, polyester resin, polyether resin, polyolefin resin (polyethylene resin, polypropylene resin etc.), polystyrene resin, polyamide resin, polycarbonate resin, acrylic resin, polyvinyl chloride resin, polyphenylene sulfide resin, polyphenylene oxide resin, polytetrafluoroethylene resin, polyimide resin, polyamide-imide resin, polyetherimide resin, polysulfone resin, polyethersulfone resin, polyketone resin, polyetherketone resin, polyetheretherketone resin, polyarylate resin, polyethernitrile resin, phenolic resin, phenoxy resin, fluororesin, urea resin, melamine resin, benzoguanamine resin, alkyd resin, epoxy resin, silicone resin, polyurethane resin, furan resin, xylene resin etc. can be cited.

[0073] Examples of the elastic material include known materials, such as polystyrene elastic materials, polyolefin elastic materials, polyurethane elastic materials, polyester elastic materials, polyamide elastic materials, polybutadiene elastic materials, polyisoprene elastic materials, fluorine-based elastic materials, and silicone elastic materials.

[0074] Examples of the rubber include well-known materials such as natural rubber (NR), styrene-butadiene rubber (SBR), acrylonitrile-butadiene rubber (NBR), nitrile rubber, hydrogenated nitrile rubber, polyisoprene rubber (IR), butadiene rubber (BR), butyl rubber (IIR), chloroprene rubber (CR), acrylic rubber (ACM), fluororubber (FKM, PTFE), silicone rubber, etc.

[0075] The weight average molecular weight of the carrier polymer material is preferably 5,000 to 15,000,000, more preferably 8,000 to 13,000,000, and further preferably 10,000 to 10,000,000. It should be noted that in this specification, the weight average molecular weight of the carrier polymer material refers to the weight average molecular weight in terms of polystyrene measured by gel permeation chromatography (GPC).

[0076] From the perspective of heat resistance, chemical resistance and durability, the carrier polymer material is preferably at least one selected from silicone resin, silicone elastic material and silicone rubber, and silicone rubber (silicone GOM) is more preferred.

[0077] The content of the carbon nanotubes in the masterbatch is preferably 0.05 to 30 Mass%, more preferably 0.1 to 25 Mass%, and further preferably 0.5 to 20 Mass%.

[0078] The masterbatch can be manufactured through the following steps.

[0079] A step of mixing a carbon nanotube dispersion liquid and a solution containing a carrier polymer material to prepare a mixed solution (mixed solution preparation step), wherein the carbon nanotube dispersion liquid contains carbon nanotubes and a solvent, and the solution containing a carrier polymer material contains a carrier polymer material and a solvent;

[0080] A step of solidifying the mixed solution to prepare a solidified product containing carbon nanotubes and a carrier polymer material (solidification step).

[0081] Hereinafter, each step will be described.

[0082] In the mixed solution preparation step, the carbon nanotube dispersion and the solution containing the carrier polymer material are mixed to prepare a mixed solution.

[0083] First, the carbon nanotube dispersion liquid will be described. Examples of the carbon nanotubes contained in the carbon nanotube dispersion liquid include the above-mentioned carbon nanotubes.

[0084] The solvent contained in the carbon nanotube dispersion liquid includes water, methanol, ethanol, n-propanol, isopropanol, tert-butanol, tetrahydrofuran, acetone, acetonitrile, etc., of which water is preferred. Water has a high dielectric constant, and by using water as a solvent, the dispersibility of the carbon nanotubes in the dispersion liquid is also good.

[0085] The carbon nanotube dispersion preferably contains an anionic dispersant. Examples of anionic groups include carboxyl, sulfonyl, phospho and salts thereof. It should be noted that carboxyl, sulfonyl and phospho can also dissociate hydrogen atoms. Examples of atoms or atomic groups constituting salts include alkali metal ions, alkaline earth metal ions, ammonium ions, onium ions of organic amines, copper ions, silver ions, aluminum ions, tin ions and the like. Specific examples of anionic dispersants include: carboxymethyl cellulose, carrageenan, pectin, gum arabic, xanthan gum, gellan gum, agar, tragacanth gum and salts thereof; anionic modified polyvinyl alcohol; anionic modified polyacrylamide and the like. Anionic dispersants are preferably carboxymethyl cellulose and salts thereof. The weight average molecular weight of the anionic dispersant is preferably 1,000 to 20,000,000. The upper limit of the weight average molecular weight is preferably 15,000,000 or less, more preferably 10,000,000 or less. The lower limit of the weight average molecular weight is preferably 10,000 or more, more preferably 50,000 or more, and further preferably 100,000 or more.

[0086] The pH of the carbon nanotube dispersion is preferably 6 to 11, more preferably 7 to 11. When the pH of the carbon nanotube dispersion is within the above range, the dispersibility of the carbon nanotubes is good. It should be noted that in this specification, the pH value is a value at 25°C.

[0087] The solid content of the carbon nanotube dispersion is preferably 0.01 to 15 Mass%, more preferably 0.05 to 10 Mass%, and further preferably 0.08 to 8 Mass%. When the solid content of the carbon nanotube dispersion is within the above range, a coagulant can be obtained more effectively. Furthermore, the dispersibility of the carbon nanotubes in the carbon nanotube dispersion is also good. In addition, the content of the carbon nanotubes in the carbon nanotube dispersion is preferably 0.01 to 10 Mass%, more preferably 0.05 to 8 Mass%, and further preferably 0.1 to 5 Mass%.

[0088] Next, the solution containing a carrier polymer material will be described. Examples of the carrier polymer material contained in the solution containing a carrier polymer material include the above-mentioned carrier polymer materials.

[0089] Examples of the solution containing the carrier polymer material include latex, emulsion, and resin particle dispersion.

[0090] As for the latex or emulsion used as the solution containing the carrier polymer material, for example, the reaction solution of the carrier polymer material such as resin, elastic material and rubber synthesized by emulsion polymerization in the presence of an emulsifier can be directly used as the latex or emulsion, or the latex or emulsion can be prepared by appropriately diluting the reaction solution or adding an emulsifier. In addition, the latex or emulsion can also be prepared by phase-transferring the reaction solution of the carrier polymer material such as resin, elastic material and rubber synthesized by solution polymerization to an aqueous system in the presence of an emulsifier.

[0091] The resin particle dispersion used as a solution containing a carrier polymer material can be prepared by dispersing the resin particles in a solvent in the presence of a surfactant or a dispersant.

[0092] Examples of the solvent contained in the solution containing the carrier polymer material include water, methanol, ethanol, n-propanol, isopropanol, tert-butanol, tetrahydrofuran, acetone, acetonitrile and the like, and water is preferred among them.

[0093] The pH of the solution containing the carrier polymer material is preferably 6-11, more preferably 7-11.

[0094] The solid content of the solution containing the carrier polymer material is preferably 0.5 to 70 Mass%, more preferably 1 to 65 Mass%, and further preferably 2 to 60 Mass%. When the solid content of the solution containing the carrier polymer material is within the above range, a coagulant can be obtained more effectively. In addition, the content of the carrier polymer material in the solution containing the carrier polymer material is preferably 0.5 to 60 Mass%, more preferably 1 to 50 Mass%.

[0095] The pH of the mixed solution obtained in the mixed solution preparation step is preferably 6-11, more preferably 7-11.

[0096] The solid content of the mixed solution obtained in the mixed solution preparation step is preferably 0.5 to 15 Mass%, more preferably 1 to 10 Mass%, and further preferably 2 to 8 Mass%. In addition, regarding the ratio of the carbon nanotubes to the carrier polymer material in the mixed solution, the carrier polymer material is preferably 200 to 9900 mass parts, more preferably 250 to 9800 mass parts, and further preferably 300 to 9700 mass parts relative to 100 mass parts of carbon nanotubes.

[0097] The coagulation step may be performed by adding an acid or a salt to the mixed solution obtained in the mixed solution preparation step.

[0098] Examples of the acid include formic acid, sulfuric acid, hydrochloric acid, and acetic acid. Examples of the salt include monovalent to trivalent metal salts such as sodium chloride, magnesium chloride, calcium nitrate, and calcium chloride. Among them, calcium chloride is preferred.

[0099] In the coagulation step, it is preferred that after adding an acid or a salt to the mixed solution, a cationic polymer as a coagulation accelerator is added to the mixed solution, or after adding a cationic polymer to the mixed solution, an acid or a salt is added to the mixed solution. Among them, it is more preferred that after adding a cationic polymer to the mixed solution, an acid or a salt is added to the mixed solution. The carbon nanotubes and the carrier polymer material are connected by the cationic polymer and then the acid or the salt is added, thereby more effectively obtaining a coagulated material.

[0100] As cationic polymers, polymers with cationic groups can be cited. As cationic groups, amino groups, ammonium groups, imino groups and their salts can be cited. As atoms or atomic groups constituting salts, hydroxide ions, halogen ions, carboxylic acid ions, sulfonic acid ions, fluorine ions, cyanide ions, silicate ions, borate ions, condensed phosphate ions, etc. can be cited. It should be noted that the amino groups cited as examples of cationic groups are not limited to -NH2, but also include substituted amino groups and cyclic amino groups. As substituted amino groups, monoalkylamino groups, dialkylamino groups, monoarylamino groups, diarylamino groups, alkylarylamino groups, etc. can be cited. As cyclic amino groups, pyrrolidinyl, piperidinyl, piperazinyl, morpholinyl, pyrrolyl, pyrazolyl, imidazolyl, pyridinyl, pyridazinyl, pyrimidinyl, pyrazinyl, oxazolyl, isoxazolyl, thiazolyl, isothiazolyl, pyrrolidonyl, piperidonyl, 3-morpholinonyl, morpholinedione groups, etc. can be cited.

[0101] The cationic polymer may be a block polymer or a random polymer. For example, there may be mentioned: a polymer having a repeating unit derived from allylamine such as polyallylamine, a condensation polymer of at least one selected from ammonia and an amine compound and epichlorohydrin, a Hofmann-modified polyacrylamide obtained by Hofmann-modifying polyacrylamide, a cationic-modified polyvinyl alcohol, etc. Among them, a polymer having a repeating unit derived from allylamine, a condensation polymer of at least one selected from ammonia and an amine compound and epichlorohydrin, etc. are preferred.

[0102] The weight average molecular weight of the cationic polymer is preferably 500 to 2,500,000, more preferably 600 to 2,000,000, and further preferably 700 to 1,500,000.

[0103] In addition, in this specification, the weight average molecular weight of a cationic polymer means the weight average molecular weight converted into polyethylene glycol measured by gel permeation chromatography (GPC).

[0104] Commercially available cationic polymers include: PAA series (polyallylamine) sold by NITTOBOMEDICAL CO., LTD.; UNISENSE (trade name) series sold by SENKA Corporation (e.g., UNISENSE FCA1000L, UNISENSE FCA 1001L, UNISENSE FCA 5000L (these are aqueous solutions of copolymers of acrylamide and diallyldimethylammonium chloride); UNISENSE FPA100L, UNISENSE FPA 101L, UNISENSE FPA 102L, UNISENSE FPA 1000L, UNISENSE FPA1001L, UNISENSE FPA 1002L (these are aqueous solutions of poly(diallyldimethylammonium chloride)); UNISENSE KHF10P (dicyandiamide-formalin condensate); UNISENSE KHP10L, UNISENSE KHP 10P (the above are dicyandiamide-diethylenetriamine condensate); UNISENSE KHE 100L, UNISENSE KHE101 L, UNISENSE KHE 102L, UNISENSE KHE 105L, UNISENSE KHE 1000L, UNISENSE KHE 1001L (the above are aqueous solutions of condensates of dimethylamine, ammonia and epichlorohydrin); UNISENSE KHE 104L (aqueous solution of condensates of dimethylamine and epichlorohydrin); UNISENSE FPV1000L (an aqueous solution of poly(methacrylic acid trimethylaminoethyl methylsulfate)); UNISENSEZCA100L (an aqueous solution of acrylate-acrylamide-diallylamine hydrochloride copolymer); DIACATCH (trade name) series sold by Mitsubishi Chemical Corporation; EPOCROS (trade name) WS-300 (an oxazoline-containing polymer) sold by Nippon Shokubai Co., Ltd., etc.

[0105] The amount of the cationic polymer added is preferably 0.01 to 10 parts by mass, more preferably 0.05 to 8 parts by mass, and further preferably 0.1 to 5 parts by mass, relative to 100 parts by mass of the solid content in the mixed solution containing the carbon nanotube dispersion and the solution containing the carrier polymer material. When the amount of the cationic polymer added is within the above range, a coagulant can be effectively obtained.

[0106] After the above-mentioned coagulation process, the generated block coagulum is separated, washed, dehydrated, and dried at a temperature of about 80 to 110°C, thereby obtaining a masterbatch. As a drying method, various drying devices such as a uniaxial extruder, an oven, a vacuum dryer, an air dryer, etc. can be used. Drying can be carried out under normal pressure, but it is preferably carried out under reduced pressure (about 10 to 1000 Pa). The drying time varies depending on the size of the dryer used, but under reduced pressure, it is usually about 30 to 180 minutes. In addition, the drying temperature is usually about 50 to 150°C.

[0107] (Base material)

[0108] The electromagnetic wave absorber of the present invention preferably contains at least one substrate selected from a resin, an elastic material and a rubber. The resin may be a thermoplastic resin or a thermosetting resin. As the resin, known materials may be cited, for example, polyester resin, polyether resin, polyolefin resin (polyethylene resin, polypropylene resin, etc.), polystyrene resin, polyamide resin, polycarbonate resin, acrylic resin, polyvinyl chloride resin, polyphenylene sulfide resin, polyphenylene ether resin, polytetrafluoroethylene resin, polyimide resin, polyamide-imide resin, polyetherimide resin, polysulfone resin, polyethersulfone resin, polyketone resin, polyetherketone resin, polyetheretherketone resin, polyarylate resin, polyethernitrile resin, phenolic resin, phenoxy resin, fluororesin, urea resin, melamine resin, benzoguanamine resin, alkyd resin, epoxy resin, silicone resin, polyurethane resin, furan resin, xylene resin, etc.

[0109] Examples of the elastic material include known materials, such as polystyrene elastic materials, polyolefin elastic materials, polyurethane elastic materials, polyester elastic materials, polyamide elastic materials, polybutadiene elastic materials, polyisoprene elastic materials, fluorine-based elastic materials, and silicone elastic materials.

[0110] Examples of the rubber include well-known materials such as natural rubber (NR), styrene-butadiene rubber (SBR), acrylonitrile-butadiene rubber (NBR), nitrile rubber, hydrogenated nitrile rubber, polyisoprene rubber (IR), butadiene rubber (BR), butyl rubber (IIR), chloroprene rubber (CR), acrylic rubber (ACM), fluororubber (FKM, PTFE), silicone rubber, and the like.

[0111] The substrate preferably contains rubber.

[0112] In addition, from the reasons of heat resistance, chemical resistance and durability, the base material is preferably at least one selected from silicone resin (silicon eresin), silicone elastomer (silicone elastomer) and silicone rubber (silicone gom), among which silicone rubber is more preferred.

[0113] When the carbon nanotubes are used in master batches, the type of the substrate may be the same type of raw material as the carrier polymer material of the master batch, or may be a different type of raw material. When silicone rubber is used as the substrate, the carrier polymer material of the master batch is preferably at least one selected from silicone resins, silicone elastic materials, and silicone rubbers, and silicone rubbers are more preferred, based on the reason that the substrate and the carrier polymer material of the master batch preferably have similar constituent components.

[0114] The content of the substrate in the electromagnetic wave absorber is preferably 60 Mass% or more, more preferably 80 Mass% or more, further preferably 90 Mass% or more, and particularly preferably 95 Mass% or more. The upper limit is preferably 99.9 Mass% or less, more preferably 99.8 Mass% or less, and further preferably 99.6 Mass% or less. In addition, when the carbon nanotubes are used in a masterbatch, the total content of the substrate in the electromagnetic wave absorber and the carrier polymer material contained in the masterbatch is preferably 60 Mass% or more, more preferably 80 Mass% or more, further preferably 90 Mass% or more, and particularly preferably 95 Mass% or more. The upper limit is preferably 99.9 Mass% or less, more preferably 99.8 Mass% or less, and further preferably 99.6 Mass% or less.

[0115] (Other additives)

[0116] The electromagnetic wave absorber of the present invention may further contain additives as required. Examples of additives include antioxidants, heat stabilizers, light stabilizers, ultraviolet absorbers, crosslinking agents, pigments, colorants, foaming agents, antistatic agents, flame retardants, lubricants, softeners, tackifiers, plasticizers, release agents, deodorants, fragrances, and the like.

[0117] The content of the additive in the electromagnetic wave absorber is preferably 30 Mass% or less, more preferably 25 Mass% or less, further preferably 20 Mass% or less, further preferably 10 Mass% or less, and particularly preferably 5 Mass% or less. The lower limit may be 0 Mass% or more, 0.01 Mass% or more, or 0.1 Mass% or more.

[0118] The electromagnetic wave absorber of the present invention can be used by being arranged on the surface of an electromagnetic wave reflecting layer such as a metal layer.

[0119] The electromagnetic wave absorber of the present invention can be used for countermeasures against radiated noise of electronic devices such as communication equipment, computers, home appliances, automotive electrical equipment, medical electrical equipment, and electromagnetic wave reflection in ETC (Electronic Toll Collection System), radar, and the like.

[0120] <Electromagnetic wave shielding complex>

[0121] The electromagnetic wave shielding composite of the present invention is characterized by comprising the electromagnetic wave absorber of the present invention and an electromagnetic wave reflecting layer provided on one surface side of the electromagnetic wave absorber.

[0122] In the electromagnetic wave shielding composite, the thickness of the electromagnetic wave absorber is preferably 0.1 to 2.0 mm, the upper limit is preferably 1.8 mm or less, more preferably 1.5 mm or less, and the lower limit is preferably 0.15 mm or more, more preferably 0.2 mm or more.

[0123] The type of the electromagnetic wave reflecting layer in the electromagnetic wave shielding composite is not particularly limited, and examples thereof include a metal layer made of a metal such as aluminum foil.

[0124] The thickness of the electromagnetic wave reflecting layer is preferably 0.005 to 1 mm, the lower limit of which is preferably 0.01 mm or more, and the upper limit of which is preferably 0.9 mm or less, and more preferably 0.8 mm or less.

[0125] In the electromagnetic wave shielding composite, an electromagnetic wave reflecting layer may be provided on one side of the electromagnetic wave absorber via an adhesive layer or a sticking layer, etc. Alternatively, an electromagnetic wave reflecting layer may be provided on one side of the electromagnetic wave absorber by a method such as sputtering or vapor deposition.

[0126] The minimum peak value of the reflection attenuation of the electromagnetic wave absorber of the present invention is preferably -15 dB or less, more preferably -20 dB or less.

[0127] The electromagnetic wave shielding composite of the present invention can be used for countermeasures against radiation noise of electronic devices such as communication equipment, computers, household appliances, automotive electrical equipment, and medical electrical equipment, and electromagnetic wave reflection in ETC (Electronic Toll Collection System), radar, and the like.

[0128] [Example]

[0129] Below, give embodiment to further specifically illustrate the present invention.Material, usage amount, ratio, processing content, processing sequence etc. shown in the following embodiment, as long as do not depart from the gist of the present invention, just can suitably change.Therefore, the scope of the present invention is not limited to the specific example shown below.

[0130] <Manufacturing of Carbon Nanotubes>

[0131] On one surface of a silicon substrate, aluminum is sputtered as a target to form a carrier film, and then, iron is sputtered as a target to form a catalyst film on the carrier film.

[0132] Next, the substrate with the catalyst film formed was placed upright in the reaction container of the CVD device. Next, the reaction container was closed, and the pressure was reduced to 1 Pa while the heater was powered on to start heating the inside of the reaction container. Next, when the temperature in the reaction container approached 700°C, nitrogen was supplied to the reaction container, and the reaction container was continuously evacuated using a pump to maintain the pressure in the reaction container at 90 kPa.

[0133] Next, the temperature in the reaction container was heated to 750°C, and nitrogen and hydrogen were supplied to the reaction container, and the pressure in the reaction container was maintained at 30 kPa. After the temperature in the reaction container reached 750°C, nitrogen, hydrogen and acetylene were supplied from the upper end of the substrate in the reaction container to the lower end along the surface of the catalyst film while preheating using the above-mentioned heater. While the pressure in the reaction container was maintained at 30 kPa, carbon nanotubes were synthesized on the substrate, thereby obtaining carbon nanotubes with a length of 0.1 to 2 mm, an average length of 2.0 mm, a number of layers of 3 to 8, an average number of layers of 6, a diameter of 5 to 12 nm, an average diameter of 9 nm, and a specific surface area of ​​225 m 2 / g, a G / D ratio of 0.8, a metal impurity content of 250 ppm, and a linear carbon nanotube with almost no waves.

[0134] It should be noted that the length of the carbon nanotubes was evaluated based on a SEM image obtained by directly photographing the substrate or photographing an object after the carbon nanotubes were cut from the substrate using a scanning electron microscope (manufactured by JEOL Ltd., model: JSM-7800F). In addition, the average length of the carbon nanotubes was obtained by randomly selecting 30 carbon nanotubes from the SEM image and calculating the average length of the 30 carbon nanotubes.

[0135] The number of layers and diameter of the carbon nanotubes were evaluated based on a TEM image obtained by directly photographing the substrate or photographing an object after the carbon nanotubes were cut from the substrate using a transmission electron microscope (manufactured by Hitachi High-Tech Corporation, model: HF2200). The average number of layers of the carbon nanotubes was obtained by selecting any 30 fields of view from the TEM image that can determine the number of layers of the carbon nanotubes, and rounding off the decimal points in the average value of the number of layers of the 30 carbon nanotubes. In addition, the average diameter of the carbon nanotubes was obtained by selecting any 30 fields of view from the TEM image, and rounding off the decimal points in the average value of the diameters of the 30 carbon nanotubes.

[0136] The specific surface area (BET value) of the carbon nanotubes was measured by a gas adsorption method (multi-point method) using a specific surface area measuring apparatus (manufactured by Shimadzu Corporation, model: 3Flex) in accordance with JIS Z8830 (ISO 9277).

[0137] The G / D ratio of the carbon nanotubes was determined using a Raman microscope (manufactured by Renishaw, model: inVia). Specifically, the G-band (1590 cm -1 ) divided by the peak intensity of the D-band (1350cm -1 )’s peak intensity.

[0138] <Production of Carbon Nanotube Dispersion>

[0139] 120 g of carboxymethyl cellulose (trade name: Cellogen WS-C, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) was dissolved in 5880 g of ion exchange water to prepare 6 kg of CMC solution. 120 g of carbon nanotubes obtained above and 23.8 kg of ion exchange water were added to the CMC solution and stirred, and then treated at 3000 rpm for 10 minutes using a chopper mixer (manufactured by FMI, Robot coupe R-10E) to prepare carbon nanotube dispersion 1.

[0140] <Manufacturing of Masterbatch>

[0141] (Production Example 1-1)

[0142] 4.5 kg of silicone elastomer emulsion (trade name: DOWSIL IE-7170, manufactured by Dow Toray Co., Ltd., solid content 48 Mass%) was added to 30 kg of carbon nanotube dispersion 1 to prepare a mixed solution. 3600 g of 2 Mass% cationic polymer (trade name: DIACATCH CHP295, manufactured by Mitsubishi Chemical Corporation, weight average molecular weight 702,000) solution was added to the mixed solution and stirred. 20% formic acid solution was then added until the mixed solution solidified. The obtained coagulant was filtered using a sieve with a mesh of 149 μm to recover the coagulant. After dehydrating the coagulant, it was dried at 110°C to produce masterbatch 1 (carbon nanotube content 5 Mass%).

[0143] (Production Example 1-2)

[0144] In 30 kg of carbon nanotube dispersion 1, 12 kg of silicone elastomer emulsion (trade name: ASAHIMRX2269, manufactured by Asahi Dyestuff Manufacturing Co., Ltd., solid content 18 Mass%) was added to prepare a mixed solution. To the mixed solution, 3600 g of 2 Mass% cationic polymer (trade name: DIACATCH CHP295, manufactured by Mitsubishi Chemical Corporation, weight average molecular weight 702,000) solution was added and stirred. A 20% formic acid solution was then added until the mixed solution solidified. The obtained coagulant was filtered using a sieve with a mesh of 149 μm to recover the coagulant. After dehydrating the coagulant, it was dried at 110°C to produce a masterbatch 2 (carbon nanotube content 5 Mass%).

[0145] <Manufacturing of electromagnetic wave absorber>

[0146] (Examples 1 to 5)

[0147] Using Labo Plastomill (trade name) (model 4C150, manufactured by Toyo Seiki Seisaku-sho, Ltd.), master batches 1 and 2 and the base material were mixed according to the mixing composition described in the following Table 1. The base material used was a material obtained by mixing 2 parts by mass of a vulcanizing agent (product name C8, manufactured by Shin-Etsu Chemical Co., Ltd.) with 100 parts by mass of silicone rubber (product name KE-951-U, manufactured by Shin-Etsu Chemical Co., Ltd.).

[0148] The obtained mixture was further mixed with a roll mill (double roll mill, manufactured by DAIHAN Co., Ltd.), and then press-formed with a hydraulic heating and cooling press (model 1811, manufactured by Imoto Seisakusho) and vulcanized to produce a sheet-shaped electromagnetic wave absorber with a thickness, length, and width of 15 cm as shown in the table below. In Table 1, the content of carbon nanotubes in the electromagnetic wave absorber is recorded in the "CNT concentration" column, and the specific gravity of the electromagnetic wave absorber is recorded in the "specific gravity" column.

[0149] <Measurement of complex permittivity>

[0150] The obtained electromagnetic wave absorber was set in a free space measuring device (Model FS-110, manufactured by Emlabo Co., Ltd.) with the film thickness direction as the incident direction of the electromagnetic wave. The transmission and reflection coefficients at 24 GHz were measured using a network analyzer (Model PNA N5290, manufactured by KEY SIGHT), and the real and imaginary parts of the complex permittivity at a frequency of 24 GHz were derived.

[0151] <Measurement of reflection loss>

[0152] Similar to the measurement of complex permittivity, the electromagnetic wave absorber was set in a free space measurement device (Model FS-110, manufactured by EM Research Institute Co., Ltd.) with the film thickness direction as the incident direction of the electromagnetic wave. According to JIS R1679, a network analyzer (Model PNA N5290, manufactured by KEY SIGHT) was used to measure the reflection attenuation of electromagnetic waves in the frequency range of 18 GHz to 45 GHz. Figure 2 The reflection attenuation of the electromagnetic wave absorber of Examples 1, 2, and 4 is shown in FIG. Figure 3 Graph 2 shows the reflection attenuation of the electromagnetic wave absorbers of Examples 3 and 5.

[0153] <Evaluation of fiber bundle>

[0154] The obtained electromagnetic wave absorber is cut in the thickness direction. The cross section of the electromagnetic wave absorber is observed using a scanning electron microscope, and the number of fiber bundles with a maximum diameter of 100nm or more (hereinafter also referred to as fiber bundle 1) and the number of fiber bundles with a maximum diameter of 5nm or more and less than 100nm (hereinafter also referred to as fiber bundle 2) present in each 10μm×10μm is counted. The number of fiber bundles 1 is recorded in the column of the number of fiber bundles 1 in the following table. In addition, the ratio (%) of the number of fiber bundles 2 to the total number of the number of fiber bundles 1 and the number of fiber bundles 2 (the ratio of the number of fiber bundles 2 / the total number of the number of fiber bundles 1 and the number of fiber bundles 2) is recorded in the column of the fiber bundle 2 ratio in the following table. It should be noted that the count value recorded in the table is the average value of the number counted for 10 squares of 10μm×10μm.

[0155] <Measurement of total light transmittance>

[0156] The total light transmittance of the electromagnetic wave absorber was measured in accordance with JIS K7236 (ISO14782) using a total light transmittance, transmission haze, and transparency measuring device (haze-gardi, manufactured by BYK Corporation).

[0157] <Measurement of elongation at break>

[0158] The elongation at break of the electromagnetic wave absorber was measured in accordance with JIS K 6251:2017.

[0159] [Table 1]

[0160]

[0161] By using the electromagnetic wave absorber of Examples 1 to 5 in communication equipment and the like, malfunctions and the like caused by electromagnetic wave interference between circuits within the equipment can be effectively suppressed.

Claims

1. An electromagnetic wave absorber comprising fibrous carbon, The electromagnetic wave absorber is characterized in that The real part of the complex permittivity of the electromagnetic wave absorber at a frequency of 24 GHz is 6 to 30, and the imaginary part is 1 to 25. When the electromagnetic wave absorber is cut, the number of fiber bundles of the fibrous carbon having a maximum diameter of 100 nm or more observed in the cut surface of the electromagnetic wave absorber is 10 or less per 10 μm×10 μm.

2. The electromagnetic wave absorber according to claim 1, characterized in that: When the electromagnetic wave absorber is cut, the ratio of the number of the fiber bundles with a maximum diameter of 5 nm or more and less than 100 nm observed in each 10 μm×10 μm of the cut surface of the electromagnetic wave absorber to the total number of the fiber bundles with a maximum diameter of 5 nm or more and less than 100 nm and the number of the fiber bundles with a maximum diameter of 100 nm or more is greater than 80%.

3. The electromagnetic wave absorber according to claim 1 or 2, characterized in that: The content of the fibrous carbon in the electromagnetic wave absorber is 0.2 to 1.5 Mass %.

4. The electromagnetic wave absorber according to claim 1 or 2, characterized in that: The electromagnetic wave absorber contains the fibrous carbon and a substrate. The substrate contains at least one selected from the group consisting of resin, elastic material and rubber.

5. The electromagnetic wave absorber according to claim 4, characterized in that: The substrate contains at least one selected from silicone resin, silicone elastic material and silicone rubber.

6. The electromagnetic wave absorber according to claim 1 or 2, characterized in that: The fibrous carbon is carbon nanotubes.

7. The electromagnetic wave absorber according to claim 1 or 2, characterized in that: The electromagnetic wave absorber contains the fibrous carbon and a substrate. The fibrous carbon is a carbon nanotube, The substrate contains at least one selected from silicone resin, silicone elastic material and silicone rubber, The content of the fibrous carbon in the electromagnetic wave absorber is 0.2 to 1.5 Mass %.

8. The electromagnetic wave absorber according to claim 1 or 2, characterized in that: The electromagnetic wave absorber has an elongation at break measured in accordance with JIS K 6251:2017 of 150% or more.

9. The electromagnetic wave absorber according to claim 1 or 2, characterized in that: The thickness of the electromagnetic wave absorber is 0.2-2.0 mm.

10. The electromagnetic wave absorber according to claim 1 or 2, characterized in that: The electromagnetic wave absorber has a specific gravity of 2.5 or less.

11. The electromagnetic wave absorber according to claim 1 or 2, characterized in that: The electromagnetic wave absorber has a total light transmittance of 20% or less as measured in accordance with ISO 13468.

12. A composite body for electromagnetic wave shielding, characterized in that: have: The electromagnetic wave absorber according to claim 1 or 2, and An electromagnetic wave reflecting layer is provided on one surface side of the electromagnetic wave absorber.